Interactions of the emerging fungus Candida auris with Acanthamoeba castellanii reveal phenotypic changes with direct implications on the response to stress and virulence - Michele Ramos Valente; Lucas Martins Alcântara; Deborah Santos Cintra; Susana Ruiz Mendoza; Elisa Gonçalves Medeiros; Kamilla Xavier Gomes; Leandro Honorato; Marcos de Abreu Almeida; Carmen Baur Vieira; Joshua Daniel Nosanchuk; Diana Bridon da Graça Sgarbi; Marcia Ribeiro Pinto; et al. (Microbiology Spectrum)
ABSTRACT Candida auris is an emerging fungal pathogen notable for its resistance to multiple antifungals and ability to survive in various environments. Understanding the interactions between C. auris and environmental protozoa, such as Acanthamoeba castellanii, could provide insights into fungal adaptability and pathogenicity. Two C. auris isolates (MMC1 and MMC2) were co-cultured with A. castellanii to examine interaction dynamics, survival, stress responses, growth, virulence, biofilm formation, and antifungal susceptibility. The association of C. auris-A. castellanii varied with a multiplicity of infection (MOI), with MMC2 exhibiting higher association rates at increased MOI than MMC1. Both isolates survived distinctly within A. castellanii, as the MMC1 showed an initial decline and subsequent increase in viability, while MMC2 maintained higher viability for up to 24 h, decreasing afterward. Both isolates exhibited accelerated growth when recovered from A. castellanii. The MMC2 isolate displayed increased resistance to oxidative, osmotic, and thermal stresses upon interaction with A. castellanii, whereas MMC1 showed limited changes. Exposure to A. castellanii also influenced the expression of virulence factors differently, with MMC1 increasing phospholipase and peptidase, while MMC2 upregulated phytase, esterase, hemolysin, and siderophores. Upon contact with A. castellanii, MMC2 enhanced biofilm formation, unlike MMC1. Both isolates increased ergosterol upon interactions, enhancing susceptibility to amphotericin B. However, both isolates were more tolerant to itraconazole and caspofungin, particularly MMC2, which showed differential expression of ergosterol biosynthesis enzymes and increased cell wall polysaccharides. This study reveals that interactions with A. castellanii modulate C. auris physiology and virulence, contributing to its environmental adaptability and resistance to antifungals.IMPORTANCECandida auris has emerged as a critical public health concern due to its resistance to multiple antifungal drugs and ability to survive on surfaces under harsh conditions, mainly due to biofilm formation. The precise origin of this emerging pathogen still awaits elucidation, but interactions with environmental protozoa may have helped C. auris to develop such virulence and resistance traits. In this work, we precisely characterize the interactions of C. auris with the free-living amoeba Acanthamoeba castellanii and how these protozoa may alter the fungal behavior in terms of virulence, thermotolerance, biofilm formation capacity, and drug resistance. It may be essential to understand the various interactions C. auris could perform in the environment, directly impacting the outcome of human infections under the One Health approach.